Profil Stres Akademik Siswa pada Implementasi Kurikulum Merdeka di SMA Negeri Kabupaten Bandung - Nissa Luthfiani Luthfiani; Muthahharah Thahir Thahir; Andre Julius (Jurnal Dimamu, 2026)
This study aims to describe the academic stress profile of 11th grade students at public high schools in Bandung Regency during the implementation of the Merdeka Curriculum for the 2024–2025 academic year. The study employs a quantitative method with a descriptive approach, involving 376 students from 14 schools, using a Likert scale questionnaire to measure five academic stressor indicators (pressure, frustration, conflict, self-imposed pressure, and self-change) and four stressor response indicators (physiological, emotional, behavioral, and cognitive). The results of the study indicate that students' academic stress levels are in the moderate category. This finding confirms that although most students are quite adaptive, there is a significant group that is still vulnerable to high pressure. This study contributes to the understanding of students' psychological dynamics in facing curriculum changes. In terms of implications, it emphasizes the importance of targeted strategies to help students manage academic stress in learning the Merdeka Curriculum.